Doing right and being good : Catholic and Protestant readings in Christian ethics - Ahearn, David Oki.; Gathje, Peter R. (Collegeville, Minn. : Liturgical Press, 2005)
"Introduces the reader to the sources of Christian ethics and to critical reflection on moral issues, including interpretations of love, justice, and the formation of a virtuous character. Selected readings discuss issues of family and sexuality, violence and peace, economic justice, abortion, and euthanasia"--Provided by publisher.
"A Michael Glazier Book"
Includes bibliographical references and indexes.
Keywords: Christian ethics